Exploring Listeria monocytogenes Transcriptomes in Correlation with Divergence of Lineages and Virulence as Measured in Galleria mellonella - Lee, Bo-Hyung (Appl Environ Microbiol, 2019)
As for many opportunistic pathogens, the virulence potential of Listeria monocytogenes is highly heterogeneous between isolates and correlated, to some extent, with phylogeny and gene repertoires. In sharp contrast with copious data on intraspecies genome diversity, little is known about transcriptome diversity despite the role of complex genetic regulation in pathogenicity. The current study implemented RNA sequencing to characterize the transcriptome profiles of 33 isolates under optimal in vitro growth conditions. Transcript levels of conserved single-copy genes were comprehensively explored from several perspectives, including phylogeny, in silico-predicted virulence category based on epidemiological multilocus sequence typing (MLST) data, and in vivo virulence phenotype assessed in Galleria mellonella. Comparing baseline transcriptomes between isolates was intrinsically more complex than standard genome comparison because of the inherent plasticity of gene expression in response to environmental conditions. We show that the relevance of correlation analyses and their statistical power can be enhanced by using principal-component analysis to remove the first level of irrelevant, highly coordinated changes linked to growth phase. Our results highlight the major contribution of transcription factors with key roles in virulence to the diversity of transcriptomes. Divergence in the basal transcript levels of a substantial fraction of the transcriptome was observed between lineages I and II, echoing previously reported epidemiological differences. Correlation analysis with in vivo virulence identified numerous sugar metabolism-related genes, suggesting that specific pathways might play roles in the onset of infection in G. mellonella. IMPORTANCE Listeria monocytogenes is a multifaceted bacterium able to proliferate in a wide range of environments from soil to mammalian host cells. The accumulated genomic data underscore the contribution of intraspecies variations in gene repertoire to differential adaptation strategies between strains, including infection and stress resistance. It seems very likely that the fine-tuning of the transcriptional regulatory network is also a key component of the phenotypic diversity, albeit more difficult to investigate than genome content. Some studies reported incongruity in the basal transcriptome between isolates, suggesting a putative relationship with phenotypes, but small isolate numbers hampered proper correlation analyses with respect to their characteristics. The present study is the embodiment of the promising approach that consists of analyzing correlations between transcriptomes and various isolate characteristics. Statistically significant correlations were found with phylogenetic groups, epidemiological evidence of virulence potential, and virulence in Galleria mellonella larvae used as an in vivo model.